Delayed nausea and vomiting from carboplatin doublet chemotherapy. (2nd June 2016) - Waqar, Saiama N.; Mann, Janelle; Baggstrom, Maria Q.; Waqar, Muhammad Atif; Chitneni, Pooja; Williams, Kristina; Gao, Feng; Morgensztern, Daniel; Govindan, Ramaswamy
Abstract: Background : Delayed nausea and vomiting following administration of carboplatin containing chemotherapy regimen remains a clinically significant problem for patients with cancer despite administration of standard antiemetic prophylaxis comprising of a 5-HT3 antagonist and dexamethasone. We performed a prospective study to define the incidence and risk factors for delayed chemotherapy-induced nausea and vomiting (CINV). Methods : Previously untreated patients with newly diagnosed cancer scheduled to receive carboplatin containing chemotherapy (AUC 5 or above), but no prophylactic aprepitant were enrolled in the study. The primary endpoint was the incidence of delayed CINV after Cycle 1 of chemotherapy. Secondary endpoints included the incidence of CINV with the third chemotherapy cycle and gender differences in incidence of CINV. Patients completed the Functional Living Index Emesis (FLIE) questionnaires 24, 48, 72 and 96 hours after receiving chemotherapy. Telephone interviews were conducted 24–48 hours following chemotherapy to assess the severity and need for breakthrough medications for CINV. Results : Between December 2006 and July 2009, 105 patients were enrolled onto this study. Delayed emesis following Cycle 1 of carboplatin was observed in 30% of patients. Of these, 14.1%, 22.4% and 23.5% of patients described CINV at 48, 72, and 96 hours, respectively. The incidence of delayed CINV following Cycle 3 dropped to 12.8%, 14.6% and 16% of patients at 48, 72 and 96 hours, respectively. No differences were observed in the incidence of CINV between men and women. A total of 20% of patients required use of breakthrough antiemetics with Cycle 1. Conclusions : Without prophylactic aprepitant administration, 30% of patients receiving carboplatin containing regimen had moderate to severe delayed CINV.